Sustaining interruption of leprosy transmission in Eswatini: lessons from years of programme transition - Mathobela Mbongiseni; Dhruv Kumar Pandey; Zulu Zulisile; Mhlanga Nhlanhla; Machekera Shepherd; Moonasar Devanand; Dlamini Nomthandazo; Tembo Susan (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Leprosy elimination programmes in low-endemic countries face a paradox: declining disease burden can weaken the surveillance, technical expertise, political commitment, and community awareness needed to sustain interruption of transmission. Eswatini, a low-endemic country in Southern Africa, transitioned over four decades from a centralized institutional model of leprosy care to integrated service delivery within primary healthcare. From 2000 to 2024, only sporadic adult cases were detected, with no child cases reported for over two decades. This paper describes lessons from sustaining elimination during this transition. Key interventions included integrating leprosy diagnosis and treatment into primary healthcare, maintaining referral-level clinical expertise, routine zero-reporting via DHIS2, case-based surveillance with household contact tracing, and embedding leprosy indicators within national neglected tropical disease policies. The programme also implemented the WHO-recommended Leprosy Elimination Monitoring Tool (LEMT) and Leprosy Programme and Transmission Assessment (LPTA) to support verification. The Eswatini experience shows that sustaining interruption in low-burden settings requires continuous surveillance, minimal technical expertise, social inclusion, sustained political commitment, and cross-border collaboration to prevent re-establishment among mobile populations. WHO-verification processes drove programme strengthening by identifying gaps and reinforcing accountability. These lessons may inform other low-endemic countries progressing toward verification and the WHO target of zero leprosy by 2030.